دراسة تصنيفية ليرقات الهاموشيات من تحت فصيلة Chironominae (Chironomidae : Diptera) في بعض الأوساط المائية العذبة شمال مدينة اللاذقية - زيني, أديب; فاضل, إقبال; رجب, إيفا (Latakia University Journal -Biological Sciences Series, 2019)
The samples of Chironominae were collected from stations differ in Physical and chemical qualities for a whole year since December 2017 till October 2018. The samples were collected from ten freshwater environments in the north of Lattakia. Five species belonging to chironominae which are Chironomus plumosus, Ch. riparious, Ch. stigmaterus, Ch. austini Ch. Dorsalis were identified . The last four species were recorded for the first time in Syrian Arab Republic. جمعت عينات الهاموشيات Chironominae من محطات متباينة بالخواص الفيزيائية والكيميائية ولمدة عام كامل من كانون أول 2017 وحتى تشرين ثاني 2018 من عشر أوساط مائية عذبة شمال مدينة اللاذقية, تم تحديد 5 أنواع تنتمي لتحت فصيلة Chironominae وهي: Chironomus plumosus, Ch. riparious, Ch. stigmaterus, Ch. austini Ch. dorsalis, وتم تسجيل الأنواع الأربعة الأخيرة لأول مرة في القطر العربي السوري.